Risk of Hepatitis B Virus Reactivation in Patients with Resolved Infection on Therapy with Corticosteroids and Conventional Synthesis Immunosuppressants for Kidney Disease: A Single-Center Analysis of 258 Patients - Han, Pingyang; Wang, Ziqiu; Wang, Zhaohui (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The risk of hepatitis B virus reactivation in patients with a previously resolved hepatitis B virus infection on therapy with corticosteroids and conventional synthesis immunosuppressants for kidney disease has not been well described. Materials and Methods: We performed a retrospective study on the risk of hepatitis B virus reactivation in patients with a previously resolved hepatitis B virus infection on therapy with corticosteroids and conventional synthesis immunosuppressants for kidney disease between January 2012 and December 2021 in the Department of Nephrology at Ruijin Hospital. Results: A total of 258 patients with a previously resolved hepatitis B virus infection [all treated with high-dose corticosteroids, of whom 192 were receiving corticosteroids combined with conventional synthesis immunosuppressant therapy, including cyclophosphamide (155), cyclosporine A (14), mycophenolate mofetil (14), and tacrolimus (9)] were enrolled. During a mean follow-up time of 21.66 months (range 9-70 months), hepatitis B virus reactivation was not observed in these patients. Conclusions: Among patients with a previously resolved hepatitis B virus infection on therapy with corticosteroids and conventional synthesis immunosuppressants for kidney disease, hepatitis B virus reactivation was not common and severe, suggesting that universal prophylaxis may not be justified or cost-effective in this clinical setting. Cite this article as: Han P, Wang Z, Wang Z. Risk of hepatitis B virus reactivation in patients with resolved infection on therapy with corticosteroids and conventional synthesis immunosuppressants for kidney disease: A single-center analysis of 258 patients. Turk J Gastroenterol. 2023;34(10):1035-1040.